Effect of phytase dosage and source on growth performance of nursery pigs - James, B.W.; Lynch, G.L.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 28-d growth assay was conducted to determine the effect of phytase dosage and source on growth performance of nursery pigs. The nine experimental treatments were control diets (0.13, 0.18, and 0.23% available phosphorus) and phytase (100, 225, or 350 FTU or FYT/kg) from either Natuphos or Ronozyme P added to the 0.13% available P diet. The results of this experiment indicate that increasing available P or phytase level, through 0.23% available P and 350 FTU or FYT/kg, respectively, improves ADG and feed efficiency. Regression analysis of the ADG response indicated that, when adding less than 350 phytase units/kg, each 100 phytase units/kg will release 0.022 and 0.017% available P for Natuphos and Ronozyme P, respectively.
Keywords: Phytase; Phosphorus; Nursery pigs; Swine